2020
DOI: 10.1038/s41398-020-00952-w
|View full text |Cite
|
Sign up to set email alerts
|

Level and timing of physical activity during normal daily life in depressed and non-depressed individuals

Abstract: Engaging in physical activity is known to reduce depressive symptoms. However, little is known which behavioral factors are relevant, and how patterns of activity change during depressive episodes. We expected that compared to controls, in depressed individuals the level of activity would be lower, the amplitude of 24-h-actigraphy profiles more dampened and daytime activities would start later. We used 14-day continuous-actigraphy data from participants in the Netherlands Study of Depression and Anxiety (NESDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 53 publications
2
70
1
5
Order By: Relevance
“…While exercise and behavioural activation may be used as adjunctive treatments in all patients with depression, sleep interventions may be especially effective in people with more self-reported somatic/vegetative and sleep symptoms. While few studies have suggested that actigraphy may serve as an objective measure of psychomotor retardation in patients with depression (Krane-Gartiser, Henriksen, Vaaler, Fasmer, & Morken, 2015), our results seem to support that physical inactivity is a general feature of depression (Burton et al, 2013) and symptom severity (Minaeva et al, 2020). This was also reflected in our analyses with individual symptoms, as over 60% of depressive symptomsacross different symptom dimensionswere associated with low GMA with moderate effect sizes.…”
Section: Discussionsupporting
confidence: 77%
“…While exercise and behavioural activation may be used as adjunctive treatments in all patients with depression, sleep interventions may be especially effective in people with more self-reported somatic/vegetative and sleep symptoms. While few studies have suggested that actigraphy may serve as an objective measure of psychomotor retardation in patients with depression (Krane-Gartiser, Henriksen, Vaaler, Fasmer, & Morken, 2015), our results seem to support that physical inactivity is a general feature of depression (Burton et al, 2013) and symptom severity (Minaeva et al, 2020). This was also reflected in our analyses with individual symptoms, as over 60% of depressive symptomsacross different symptom dimensionswere associated with low GMA with moderate effect sizes.…”
Section: Discussionsupporting
confidence: 77%
“…However, we found no association with the timing of the activity. Instead, our functional data-driven models showed similar associations as were found in our previous analyses on NESDA data [7,8], indicating that current depressive and/or anxiety disorders and more severe symptoms were associated with lower physical activity levels but not with a preference for eveningness. These results suggest that the use of daily indices of motor activity may be sufficient when studying the association with psychopathology.…”
Section: Comparison With Previous Literaturesupporting
confidence: 82%
“…Research indicates that disruptions in circadian activity rhythms, especially daily motor activity patterns, correlate with poor mental [4] and physical [5] health. Burton et al [6] and our recent results showed that a low level of daily motor activity is associated with depressive [7,8] and anxiety [7] disorders. In addition, sociodemographic and lifestyle factors, especially age and BMI, have been linked to disruptions in daily motor activity patterns.…”
Section: Introductionmentioning
confidence: 53%
“…Os efeitos da pandemia foram que houve aumento na carga global de estresse, ansiedade, sintomas depressivos, insônia, negação, raiva e medo (52,54,65) e há a preocupação de que a próxima pandemia seja em saúde mental (66). Tais agravos em saúde mental, por sua vez, associam-se à imunodepressão(67,68) e associam-se a baixos níveis de atividade física (69)(70)(71).…”
Section: Agravos à Saúde Mentalunclassified
“…É importante destacar que a relação entre nível de atividade física e saúde mental é bidirecional, isto significa que tanto maiores níveis de atividade física associam-se a menos sintomas em saúde mental(83) e mais sintomas em saúde mental levam a menores níveis de atividade física (69)(70)(71), o que sugere que, para quebrar a inércia a fim de romper o ciclo vicioso, é preciso maior esforço por parte do indivíduo. A literatura mostra que, tendo vencido a inércia e conseguido engajar-se na esportesatividade física ocupacional, atividade física no lazer e atividade física em locomoção (81).…”
Section: O Uso De Máscaras Durante a Prática De Atividade Físicaunclassified